Application of Online Project-Based Worksheets in the Utilization of Wood Sawdust as Adsorbents in Industri Liquid Waste Treatment - Sukmawardani, Yulia; Meisani, Riseu; Subarkah, Cucu Zenab; Ida Farida (Orbital: Jurnal Pendidikan Kimia, 2024)
This study aims to analyze performance and students' higher-order thinking skills after implementing project-based worksheets on sawdust as an adsorbent in industrial waste treatment. The research method used is a pre-experiment with a one-shot case study design. The subjects of this study were chemical education students at UIN Sunan Gunung Djati Bandung who took the chemical separation course. The instruments used are learning descriptions, worksheets, and higher-order thinking skills. The results showed that the average value of student performance in completing the bold project-based worksheets was 92.6, with an outstanding category. The highest average score achieved was in phase 3 of designing the project, with 96.5, an exceptional category. In the excellent category, the lowest average score in phase 4 of compiling product drafts/prototypes was 83.75. The results of students' higher-order thinking skills obtained an average value of 82.2, with an outstanding category. Thus, the bold application of project-based worksheets on using sawdust as an adsorbent in industrial wastewater treatment can develop high-order thinking skills in students.